Spectrum of giant cells and its significance on FNAC in breast lesions - S Dayal; M Mathur; V Gupta (Association of Clinical Pathologists of Nepal, 2017)
Fine needle aspiration of breast is being performed from last several years. It is not uncommon to find giant cell on FNAC of breast smears .Giant cells arises from monocyte / macrophage lineage which are capable of fusion to form multinucleated giant cell. The common giant cell seen in breast on fna smears are foreign body , Langhan's type , stromal giant cells , tumor giant cells and osteoclastic giant cell . It arises in benign as well as malignant lesions of the breast. Hence, their recognition and correct interpretation can be valuable to cyto pathologist who identifies the variation in diagnosis of pathology and to the clinician for the treatment modalities of different breast pathologies.